Increased prevalence of indoor Aspergillus and Penicillium species is associated with indoor flooding and coastal proximity: a case study of 28 moldy buildings. Issue 11 (1st October 2021) - Omebeyinje, Mayomi H.; Adeluyi, Adewale; Mitra, Chandrani; Chakraborty, Paramita; Gandee, Gregory M.; Patel, Nalit; Verghese, Bindhu; Farrance, Christine E.; Hull, Matthew; Basu, Paramita; Lee, Kwonmoo; Adhikari, Atin; et al.
Abstract : Indoor dampness causes mold growth. The likelihood of such molds being clinically relevant Aspergillus and Penicillium spp . is higher in coastal homes with history of indoor flooding. Fungal surveillance in flood prone homes is therefore critical. Abstract : Indoor flooding is a leading contributor to indoor dampness and the associated mold infestations in the coastal United States. Whether the prevalent mold genera that infest the coastal flood-prone buildings are different from those not flood-prone is unknown. In the current case study of 28 mold-infested buildings across the U.S. east coast, we surprisingly noted a trend of higher prevalence of indoor Aspergillus and Penicillium genera (denoted here as Asp–Pen) in buildings with previous flooding history. Hence, we sought to determine the possibility of a potential statistically significant association between indoor Asp–Pen prevalence and three building-related variables: (i) indoor flooding history, (ii) geographical location, and (iii) the building's use (residential versus non-residential). Culturable spores and hyphal fragments in indoor air were collected using the settle-plate method, and corresponding genera were confirmed using phylogenetic analysis of their ITS sequence (the fungal barcode). Analysis of variance (ANOVA) using Generalized linear model procedure (GLM) showed that Asp–Pen prevalence is significantly associated with indoor flooding as well as coastal proximity. To address the small sample size, a multivariate decision tree analysis was conducted, which ranked indoor flooding history as the strongest determinant of Asp–Pen prevalence, followed by geographical location and the building's use.